Pengaruh Ukuran Dewan Dan Jumlah Rapat Dewan Direksi Terhadap Firm Value Dengan Corporate Environmental Disclosure Sebagai Variabel Intervening - Kamilla, Puteri (International Journal Labs, 2025)
This research aims to investigate the impact of corporate governance on firm value through corporate environmental disclosure. The GRI Index is used to obtain the value of corporate environmental disclosure and firm value assessment using the Tobins Q ratio. This study used variance-based structural equation modeling technique (PLS-SEM) with WarpPLS 5.0 software to analyze the data. The results of the study show that corporate governance assessed through the size of the board and the number of board of directors meetings has a significant positive relationship with corporate environmental disclosure and firm value. In addition, corporate environmental disclosure has a mediating effect on the size of the board and the frequency of board of directors meetings on firm value. In conclusion, the implementation of corporate governance can provide a higher value of corporate environmental disclosure so that it provides better firm value.